Quantifying Crime Prevention Potential of Near-Repeat Burglary. (September 2019) - Groff, Elizabeth; Taniguchi, Travis
The space-time risk window associated with near-repeat burglary patterns would seem to present a natural opportunity for burglary prevention efforts. However, constraints associated with the reporting of, police response to, and space-time patterning of burglaries can reduce the crime prevention potential of such efforts. To better estimate the crime prevention potential of focusing on near-repeat burglaries, we studied burglary patterns in 10 U.S. cities. Descriptive aspatial and spatial statistics were used to answer the research questions. Significant space-time clustering does not necessarily indicate an actionable near-repeat problem. Police analysts and researchers should also consider the crime prevention potential of focusing on near repeats—in other words, the proportion of burglaries that are preventable. The results of this test provide new information to guide the implementation and evaluation of crime prevention efforts focused on near-repeat events.